Socio-demographic characteristics of basic life support course participants in Denmark. (January 2022) - Jensen, Theo Walther; Folke, Fredrik; Andersen, Mikkel Porsborg; Blomberg, Stig Nikolaj; Jørgensen, Anne Juul; Holgersen, Mathias Geldermann; Ersbøll, Annette Kjær; Hendriksen, Ole Mazur; Lippert, Freddy; Torp-Pedersen, Christian; Christensen, Helle Collatz
Abstract: Background: Bystander-initiated basic life support (BLS) plays an important role in improving survival after out-of-hospital cardiac arrest. In 2009, laws mandating BLS course participation when acquiring a driver's licence were implemented in Denmark. The aim of this study was to characterise Danish BLS course participants. Methods: This study is a Danish, registry-based, follow-up study that examined all Danish BLS course participants from 2016 to 2019. Data concerning BLS course participation were supplied by the major Danish BLS course providers. Socio-economic and healthcare data on all Danish inhabitants were assessed using national registers from Statistics Denmark. Results: Between January 1, 2016, and January 1, 2020, 3.6% of the entire adult population of Denmark attended certified BLS courses annually. Since the implementation of a law mandating BLS course participation when acquiring a driver licence in 2009, approximately 44% of the adult population has participated in a BLS course. BLS course participants were commonly younger and healthier than the general population (mean 31.3 years old vs. 51.3 years old, P < 0.001). Furthermore, law-mandated BLS course participants had a lower disposable income (adjusted OR: 0.23; 95% CI: 0.23–0.23; P < 0.001) and were more likely to live in rural areas (adjusted OR: 0.57; 95% CI: 0.57–0.58; P < 0.001). Conclusion: In Denmark, 3.6% of the entire adult population attend certified courses annually. BLS participants are commonly male, younger, healthier, less likely to have small children in the household, and more likely to live in rural areas. Law-mandated BLS course participation prior to acquiring a driver's licence has been successful in reaching segments of the society that are known to have limited participation.